Biofilm Adhesion to Surfaces is Modulated by Biofilm Wettability and Stiffness. Issue 5 (15th January 2021) - Kretschmer, Martin; Schüßler, Carina Anke; Lieleg, Oliver
Abstract: Although many surfaces in industry and medicine are colonized by bacterial biofilms, little is known about the physical principles that govern the adhesion properties of such bacterial communities. In part, this is due to the technical challenge associated with the characterization of a biofilm directly on the substrate it is grown on. Moreover, distinguishing between the cohesive and adhesive properties of a (bio)material requires information on the amount of material transferred between the interacting surfaces, which is not easily possible in existing measurement techniques applied in biofilm research. Here, a new method is introduced which allows for characterizing the detachment process of biofilms in situ and makes it possible to identify the dominant mode of fracture. As a countersurface in those detachment tests with biofilm layers, either a synthetic/inorganic material surface or another biofilm layer can be used. By comparing results obtained with different biofilms generated at distinct cultivation conditions, how two selected material properties, i.e., the biofilm wettability and the biofilm stiffness, contribute to the detachment process can be shown. The novel measurement approach demonstrated here can easily be adapted further to enable adhesion/detachment measurements with a broad range of other biofilms including those grown at submerged conditions. Abstract : The detachment process of bacterial biofilms in situ is characterized. With this approach, it is possible to identify the dominant mode of fracture and to disentangle the contribution of two material properties, i.e., the biofilm wettability and biofilm stiffness, to the detachment process.